Isotopi Dalam Kumpulan Puisi Aku Ini Binatang Jalang Karya Chairil Anwar: Kajian Analisis Wacana - Pelangi, Inne (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Indonesia, as a country with diverse ethnicities and cultures, requires effective communication tools to This research aims to describe the isotopes found in the Poetry Collection